Novel evidence suggests that a 'Rickettsia felis‐like' organism is an endosymbiont of the desert flea, Xenopsylla ramesis. Issue 6 (6th March 2015) - Rzotkiewicz, Sabine; Gutiérrez, Ricardo; Krasnov, Boris R.; Morick, Danny; Khokhlova, Irina S.; Nachum‐Biala, Yaarit; Baneth, Gad; Harrus, Shimon
Abstract: Fleas are acknowledged vectors and reservoirs of various bacteria that present a wide range of pathogenicity. In this study, fleas collected from wild rodents from the Negev desert in southern Israel were tested for Rickettsia DNA by targeting the 16S rRNA ( rrs) gene. Thirty‐eight Xenopsylla ramesis, 91 Synosternus cleopatrae and 15 Leptopsylla flea pools (a total of 568 fleas) were screened. Rickettsia DNA was detected in 100% of the X. ramesis and in one S. cleopatrae flea pools. None of L. algira flea pools was found positive. All positive flea pools were further characterized by sequencing of five additional genetic loci ( gltA, ompB, ompA, htrA and fusA ). The molecular identification of the positive samples showed all sequences to be closely related to the ' Rickettsia felis ‐like' organisms (99–100% similarities in the six loci). To further investigate the association between ' R. felis ‐like' and X. ramesis fleas, ten additional single X. ramesis adult fleas collected from the wild and five laboratory‐maintained X. ramesis imago, five larva pools (2–18 larvae per pool) and two egg pools (18 eggs per pool) were tested for the presence of ' R. felis ‐like' DNA. All samples were found positive by a specific ompA PCR assay, confirming the close association of this Rickettsia species with X. ramesis in all its life stages. These results suggest a symbiotic association between ' Rickettsia felis ‐like' and X. ramesis fleas.